2021
DOI: 10.3390/lubricants9010010
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Approaches to the Design of Floating-Liner Apparatus for Instantaneous Piston Assembly Friction Measurement

Abstract: Several approaches have been developed to measure instantaneous friction between the piston assembly and cylinder in internal combustion (IC) engines, such as floating-liner, reciprocating liner, instantaneous mean effective pressure (IMEP), fixed sleeve, and (P-ω) method and tribological bench tests. However, the “floating-liner method” and the “(IMEP) method” are the most common methods used to measure instantaneous friction between the piston assembly and IC engines. This paper critically evaluates differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…There are many studies focused on decreasing the friction within the internal combustion engine without upgrading the piston rings. Such as, Abdelrahman M. Youssef et al [12] showed the most common techniques used in the design of floating-liner systems for measuring piston assembly friction. They reached several conclusions that the most common type of floating liner systems is the pressurized system due to their capability to simulate the entirety of conditions that exists in a firing engine during operation, and non-pressurized floating liners are decent at simulating engines at low intensity of load and are easy to manufacture and use.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies focused on decreasing the friction within the internal combustion engine without upgrading the piston rings. Such as, Abdelrahman M. Youssef et al [12] showed the most common techniques used in the design of floating-liner systems for measuring piston assembly friction. They reached several conclusions that the most common type of floating liner systems is the pressurized system due to their capability to simulate the entirety of conditions that exists in a firing engine during operation, and non-pressurized floating liners are decent at simulating engines at low intensity of load and are easy to manufacture and use.…”
Section: Introductionmentioning
confidence: 99%